2001
DOI: 10.1007/s002100000372
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of oxytocin cause vasoconstriction by activating vasopressin V 1A receptors in the isolated perfused rat kidney

Abstract: The aim of this study was to evaluate the renal vascular effects of oxytocin in Sprague-Dawley rats and in Brattleboro heterozygous or homozygous rats, the latter being genetically deficient in vasopressin synthesis. Studies were performed in vitro, in the isolated kidney perfused in an open circuit with a Tyrode's solution. Oxytocin induced a concentration-dependent renal vasoconstriction in Sprague-Dawley rats, at rather high concentrations (EC50=170+/-39 nM, mean +/- SEM, n=6) with a maximum response amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The clinical application of OT-GKR in this pathology could be safe because of the specific interaction with OTR and V1aR, as described in the present study. The weaker effects of OT-X than OT on uterine contractions have already been reported [45], and OT replacement by OT-GKR in the therapy of cardiac pathologies could reduce vasoconstriction attributed to V1aR activation by OT [46].…”
Section: Discussionmentioning
confidence: 80%
“…The clinical application of OT-GKR in this pathology could be safe because of the specific interaction with OTR and V1aR, as described in the present study. The weaker effects of OT-X than OT on uterine contractions have already been reported [45], and OT replacement by OT-GKR in the therapy of cardiac pathologies could reduce vasoconstriction attributed to V1aR activation by OT [46].…”
Section: Discussionmentioning
confidence: 80%
“…In previous studies reported in the literature, Oxytocin has been shown to play an important role in the regulation of the vascular compartment: it causes vasodilatation in the pre-constricted pulmonary vasculature [23] and induces renal vasoconstriction in rats by activating vasopressin V1A receptors [24]. Moreover, pharmacological studies have shown the existence of Oxytocin receptors in human umbilical vein endothelial cells (HUVEC); the interaction between Oxytocin and its receptor causes Figure 3.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 90%
“…Oxytocin also stimulates renin secretion, perhaps by an increase in the renal sympathetic nerve activity (Huang et al 2000). Additionally, in homozygous Brattleboro rats that are genetically deficient in endogenous vasopressin, oxytocin elicited V 1a receptor‐mediated renal vasoconstriction, in which oxytocin acted as a partial agonist with a low apparent potency (Loichot et al 2001). The blood volume expansion in response to HS during experimental septic shock induced by CLP stimulated oxytocin secretion, but the administration of the oxytocin receptor antagonist did not alter the pressor response, suggesting that oxytocin does not participate in this response.…”
Section: Discussionmentioning
confidence: 99%